Revisiting Rural Women's History - Ambrose, Linda M.; Devine, Jenny Barker; Whayne, Jeannie (Agricultural history, 2015)
According to colby, improving their cultural circumstances was an important aspect of enhancing women's satisfaction and happiness but that alone was insufficient. education was crucial, both in terms of eliminating their basic ignorance of farm economics and their isolation from literature, an isolation that undermined their spiritual wellbeing.